2017
DOI: 10.14309/00000434-201710001-00127
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Aspirin Use and Mortality in Colorectal Cancer

Abstract: Background: Aspirin use lengthens survival in patients with colorectal cancer (CRC). We aimed to add to the evidence examining this relationship and to compare the survival benefit between aspirin started before CRC diagnosis with those started after CRC diagnosis. Methods:The study involved 173 consecutive patients who had a histopathologic diagnosis of colorectal carcinoma between 1996 and 2014. The electronic medical record was used to collect data on demographic characteristics (age, sex, and race), family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A number of authors give estimates of the association with aspirin in terms of the duration of the additional survival in patients taking the drug. Thus, Albandar [117] who followed 174 US veterans with colorectal cancer to death reported that the median survival of patients taking aspirin was 941 versus 384 days in those not taking aspirin. Several papers record an increased survival associated with aspirin taken by patients with liver cancer: in one 18 months additional survival [93]; in another 6% more patients survived 10 years with aspirin after diagnosis [103], and the median overall survival period after embolisation was longer for patients taking aspirin (57 versus 23 months) [119].…”
Section: Mortalitymentioning
confidence: 99%
“…A number of authors give estimates of the association with aspirin in terms of the duration of the additional survival in patients taking the drug. Thus, Albandar [117] who followed 174 US veterans with colorectal cancer to death reported that the median survival of patients taking aspirin was 941 versus 384 days in those not taking aspirin. Several papers record an increased survival associated with aspirin taken by patients with liver cancer: in one 18 months additional survival [93]; in another 6% more patients survived 10 years with aspirin after diagnosis [103], and the median overall survival period after embolisation was longer for patients taking aspirin (57 versus 23 months) [119].…”
Section: Mortalitymentioning
confidence: 99%
“…Aspirin is a non-steroidal anti-inflammatory drug whose primary active component is acetylsalicylic acid (16). Aspirin is clinically used to decrease fever, inflammation, cardiovascular disease and certain types of cancer (17)(18)(19). Jiang et al (20) described the association between the use of aspirin and liver fibrosis in 1,856 patients with chronic liver disease in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cohort study by Loomans‐Kropp et al involving over 140 000 individuals enrolled in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial found that aspirin use at least three times per week was associated with reductions in all‐cause cancer mortality 23 . In veterans, a similar prognostic benefit has been demonstrated in those with colorectal cancer who regularly used aspirin, even after adjusting for age and cancer stage 24 . The protective effect of aspirin and other NSAIDs on survival extends to patients with head and neck cancer as well 13,14 …”
Section: Discussionmentioning
confidence: 94%
“…23 In veterans, a similar prognostic benefit has been demonstrated in those with colorectal cancer who regularly used aspirin, even after adjusting for age and cancer stage. 24 The protective effect of aspirin and other NSAIDs on survival extends to patients with head and neck cancer as well. 13,14 Aspirin and other NSAIDs act via the PI3K signaling pathway, which is crucial to cell growth and survival in both the physiologic and pathologic state.…”
Section: Discussionmentioning
confidence: 99%